Letter from B. Hoff to James Curtis Booth, February 8, 1855 - Hoff, B. (1855)
B. Hoff writes to commiserate on the poor health of James Curtis Booth's (1810-1888) mother.
Keywords: Booth, James Curtis, 1810-1888